IDENTIFIKASI BAKTERI Escherichia coli PADA SUSU KEDELAI TIDAK BERLABEL - Kamil Kamil (Jurnal Medika : Karya Ilmiah Kesehatan, 2017)
Background: Based on the data of sikda (local health information system) diarrhea is still one of the major health problems suffered in Samarinda City. Even in some villages, this type of health problem ranks the third most suffered disease. Diarrhea is a disease which is caused by fecal bacteria. Escherichia coli bacteria can be used as an indicator of contamination in water and food or drink by the bacteria derived from feces. This bacterium can spread through various ways, among others is through contaminated water and food or drink. This research aims to test the existence of Escherichia coliin unlabeled soya milk in Samarinda City. Methods: This research used 7 samples of unlabeled soya milk to prove the existence of Escherichia coliwith the stages that included presumptive test and confirmed test. Presumptive test used media Mac conkey and confirmed test used IMVIC method. Findings: The result of the research showed that all samples tested were negative of Escherichia coli. However, 3 samples of soya milk contained Klebsiella pneumonia andKlebsiella ozaenae Conclusion:It is concluded in this research that there was noEscherichia coli bacteria found in the samples of unlabeled soya milk so that they have met the Indonesia National Standard, SNI Number 7399-2009 and Minister of Health Regulation Number 1096/Menkes/Per/2011. However, there were other types of bacteria found, namely Klebsiella pneumonia andKlebsiella ozaenaebacteria.